Some strategies for utilization of rice bran functional lipids and phytochemicals - Phumon Sookwong (2018)
© 2018 by Japan Oil Chemists’ Society. Rice bran contains a great amount of functional lipids and phytochemicals including γ-oryzanols, tocotrienols, and tocopherols. However, utilization of those compounds is limited and needs some proven guidelines for better implementation. We introduce some effective strategies for the utilization of rice functional lipids, including an introduction of pigmented rice varieties for better bioactive compounds, biofortification of rice tocotrienols, plasma technology for improving rice phytochemicals, supercritical CO2extraction of high quality rice bran oil, and an example on the development of tocotrienol-fortified foods.